ASSOCIATION OF CARDIOVASCULAR OUTCOME WITH THE SLOPE BETWEEN SYSTOLIC BLOOD PRESSURE AND PULSE RATE MEASURED BY AMBULATORY BLOOD PRESSURE MONITORING IN A JAPANESE GENERAL PRACTICE. (April 2021) - Narita, Keisuke; Satoshi, Hoshide; Kazuomi, Kario
Abstract : Objective: Blood pressure (BP) and pulse rate (PR) usually show a physiologically negative correlations in terms of keeping cardiac output consistent. The relationship between BP and PR is associated with sympathetic activity. The higher PR corresponding to elevated BP measured by home BP monitoring reportedly elevates cardiovascular disease (CVD) risks. However, it remains unclear whether the relationship between ambulatory BP and PR predicts incident of CVD. We aimed to assess the predictive ability of the correlations between BP and PR for incident of CVD in clinical practice. Design and method: This is a prospective study, which recruited patients with a history of or risk factors of CVD. Participants underwent ambulatory BP monitoring and followed-up incident CVD, including stroke and coronary artery disease. The relationship between BP and PR was evaluated by the slope of correlation line between systolic BP (SBP) and PR in 24-hour, daytime, and nighttime which were assessed by each participant's diary. The association of the slope between SBP and PR with incident of CVD was assessed using Cox proportional hazards models. Results: Among 1422 participants (age, 64.6 ± 11.6 [mean ± SD], 47.6% male, 92.8% hypertensives), During a follow-up of 6.8 ± 3.5 years (9670 person-years), 49 stroke, 53 coronary artery disease (CAD), and 125 various CVD events (stroke, CAD, hospitalization due to heart failure, and aortic dissection) occurred. Although the slope between SBP and PR in daytime did not associated with CVD risks after adjustments for covariates, the slope between SBP and PR in nighttime was associated with an increase risk of stroke and various CVD events after adjustments for covariates (hazard ratios [95%CIs] for stroke: 1st quartile as reference; 2nd quartile, 1.45 [0.57–3.72]; 3rd quartile, 1.50 [0.60–3.74]; 4th quartile, 2.53 [1.05–6.11]; for various CVD events: 1st quartile as reference; 2nd quartile, 1.43 [0.83–2.47]; 3rd quartile, 1.56 [0.91–2.70]; 4th quartile, 1.96 [1.13–3.38]) (Table). Figure. No caption available. Conclusions: Based on the results of this study, the slope between SBP and PR in nighttime was suggested to be associated to CVD outcomes.